1994
DOI: 10.1104/pp.104.2.479
|View full text |Cite
|
Sign up to set email alerts
|

A Contrast of the Plasma Membrane Lipid Composition of Oat and Rye Leaves in Relation to Freezing Tolerance

Abstract: l h e lipid composition of the plasma membrane isolated from leaves of spring oat (Avena safiva 1. cv Ogle) was vastly different from that of winter rye (Secale cereale 1. cv Puma). l h e plasma membrane of spring oat contained large proportions of phospholipids (28.8 mol% of the total lipids), cerebrosides (27.2 mol%), and acylated sterylglucosides (27.3 mol%) with lesser proportions of free sterols (8.4 mol%) and sterylglucosides (5.6 mol%). In contrast, the plasma membrane of winter rye contained a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(182 citation statements)
references
References 49 publications
5
175
0
2
Order By: Relevance
“…Interestingly, the proportions of SG and ASG in PM differ greatly depending on the plant species and the growth conditions, varying from 8% SG plus ASG in Arabidopsis thaliana leaves to 6% SG and 27% ASG in spring oat (Avena sativa) leaf (102,103). The similar ability of conjugated and free forms of phytosterols alone to order membrane evidenced in this study (Fig.…”
Section: Free and Conjugated Phytosterols Exhibit Various Abilities Tsupporting
confidence: 52%
“…Interestingly, the proportions of SG and ASG in PM differ greatly depending on the plant species and the growth conditions, varying from 8% SG plus ASG in Arabidopsis thaliana leaves to 6% SG and 27% ASG in spring oat (Avena sativa) leaf (102,103). The similar ability of conjugated and free forms of phytosterols alone to order membrane evidenced in this study (Fig.…”
Section: Free and Conjugated Phytosterols Exhibit Various Abilities Tsupporting
confidence: 52%
“…Through the cold acclimation process, reprogramming of gene expression and various modifications in the metabolism take place (Chinnusamy et al 2010). Acclimation also causes an increase in the production of antioxidants, abscisic acid (ABA) and compatible osmolytes such as soluble sugars and proline (Lynch & Steponkus 1987;Koster & Lynch 1992;Chen et al 1993;Kishitani et al 1994;Uemura & Steponkus 1994;Murelli et al 1995;Nomura et al 1995;Dörffling et al 1997;Tao et al 1998). Denesik (2007) reported that cold treatment affects membrane fluidity resulting in an increase in the membrane rigidity.…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…Cold acclimation of winter rye (Secale cereale) seedlings showed an increase in free sterol content, with β-sitosterol having the largest increase (Lynch & Steponkus, 1987). Uemura and Steponkus (1994) also found an increase of β-sitosterol with cold acclimation in winter rye; however, these results were not mimicked in spring oats (Avena sativa L. cv Ogle), where there was no significant change in β-sitosterol, but the stigmasterol proportion increased, whilst cholesterol decreased.…”
Section: Sterolsmentioning
confidence: 55%
“…Changes in phospholipid and sterol composition were found in Arabidopsis thaliana after cold acclimation at 2°C for one week, which increased its freezing tolerance from -2°C down to -10°C (Uemura et al, 1995). Cell membrane phospholipid changes were also observed in oat leaves (Uemura & Steponkus, 1994). These changes may be related to improved membrane stability in these plants.…”
Section: Preconditioning and Cold Acclimationmentioning
confidence: 72%
See 1 more Smart Citation